Evaluation Of The Use Of Facilities In Port Of Fisheries Nusantara Sungailiat Bangka Belitung Province - Kholijah '; Syaifuddin '; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in December 2013 at the street Yos Sudarso Number.50 Village Sungailiat, District Sungailiat, Bangka, Bangka Belitung Province. The purpose of this study was to determine the types of facilities as well as the size and condition of the facilities in the archipelago Sungailiat fishing port, determine the level of utilization of fishing port facilities in the archipelago Sungailiat and find solutions to the problems of utilization of fishing port facilities in the archipelago Sungailiat. While the benefits are expected to know the truth from the facility, activity in the archipelago Sungailiat fishing port as well as a source of information for the fishing port of the archipelago and the subsequent research, especially in areas related ie Evaluation Utilization Facilities Archipelago Fishery Port Sungailiat province of Bangka Belitung. Facilities that have analyzed the utilization rate is 26.57% pier, harbor pool facilities, spacious pools to the port that is 95.29%, while the depth of the pool is 129% port, the fuel tank facilities utilization rate is 4.78%, the ice needs facilities utilization rate was 81.42%, and freshwater facilities utilization rate is 126.90%.Keywords: Facility Type, Condition of Facilities, Facilities Utilization Rate, Fishing Port Facilities Archipelago Sungailiat